Obituary: Khaled Al Siddiq. Issue 2 (1st December 2021) - Unknown
Abstract : On behalf of the Scientific Committee of Anthropology of the Middle East, we would like to express our deepest regrets for the loss of pioneer film maker Khaled Al Siddiq on October 14th, 2021. Khaled Al Siddiq's 1972 film, Cruel Sea won the Fipresi Prize at the Venice Film Festival and was also a prize winner at the Syrian Film Festival that year. This landmark film bought the Gulf Cinema Company, where Khaled was the director, widespread international acclaim. Al Siddiq's other important films include The Wedding of Zein (1976) and Shaheen (1984). Our deepest condolences go to Dr. Zubeydenh Ashkanani, his wife, whose generous gift of the yearly eponymous prize awarded for best article of the year in the Anthropology of the Middle East is always well-received and much appreciated.